Impact of hypertension on liver fibrosis in patients with metabolic dysfunction-associated fatty liver disease - Gao, Zhifeng; Deng, Huan; Qin, Bowen; Bai, Liang; Li, Jiangwei; Zhang, Jian (Frontiers in Medicine, 2025)
BackgroundThis study aims to evaluate the association between hypertension and the risk of fibrosis in metabolic dysfunction–associated steatotic liver disease (MASLD) patients, as well as to investigate the impact of hypertension on the progression of liver fibrosis within this population.MethodsWe utilized data from the NHANES 2017 to March 2020. Multivariate logistic regression models were employed to control for sociodemographic and metabolic factors to determine the associations between hypertension, MASLD, and fibrosis.ResultsOf the total cohort (N = 5,967) 57.92% had hypertension, 38.8% had MASLD, 25.88% had both MASLD and hypertension. Patients with MASLD were more likely to have hypertension (64.24% vs. 44.80%). There was a significant association between stage I (OR1.70, 95% CI: 1.15–2.53) and stage II hypertension (OR1.98, 95% CI: 1.38–2.85) and an increased risk of SF. After adjusting for multiple confounding factors, stage I (OR1.59, 95% CI: 1.09–2.24) and stage II hypertension (OR1.48, 95% CI: 1.06–2.06) remained significantly associated with the risk of SF. Patients with both MASLD and hypertension had higher rates of SF at 14.83% and AF at 7.47%. After adjusting for sociodemographic factors, those patients still had an 8.02-fold increased risk of SF (OR8.02, 95% CI: 4.47–14.39) and a 15.13-fold increased risk of AF (OR15.13, 95% CI: 7.09–32.3). Further adjustment for metabolic factors, those patients still had a significantly higher risk of SF (OR3.07, 95% CI: 1.83–5.14) and AF (OR4.01, 95% CI: 1.48–10.89).ConclusionMASLD and hypertension are at risk for fibrosis, and the coexistence of the two has a more significant impact on the risk of fibrosis.